1934
DOI: 10.1073/pnas.20.4.221
|View full text |Cite
|
Sign up to set email alerts
|

Fused “Onium” Salts as Acids

Abstract: A study by Franklin, Kraus and their co-workers of many different reactions' in liquid ammonia as solvent has served to establish definitely the existence of a series of ammond-compounds which are derived from ammonia, as the parent substance, in much the same way that the usual acids, bases and salts are related to water. Other investigators have shown that this behavior is by no means limited only to water and ammonia as solvents. Many other substances, such as hydrazine, hydrogen sulphide, hydroxylamine, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1943
1943
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Unlike Cl, metals may affect AN decomposition more as reaction partners than as catalysts . Audrieth and Schmidt viewed that Cu acts as a reaction partner (ie, it is consumed and is not just a catalyst) and suggested that some other metals may react similarly:…”
Section: Reactions Involving Additional Substancesmentioning
confidence: 99%
“…Unlike Cl, metals may affect AN decomposition more as reaction partners than as catalysts . Audrieth and Schmidt viewed that Cu acts as a reaction partner (ie, it is consumed and is not just a catalyst) and suggested that some other metals may react similarly:…”
Section: Reactions Involving Additional Substancesmentioning
confidence: 99%
“…The slow reactions of nanometals in mixtures with AN under DSC are largely determined by the reactivity of their oxide films and metals themselves with the AN melt. n-Cu and n-Ni and their oxides, as well as n-Mo, are reacted with AN melt in the temperature range from 250 to 300°C with the release of heat and formation of nitrates and metal oxides soluble in AN melt (except MoO 3 [33]). For n-Zn, the small exothermal peak in the temperature range 320-340°C was followed by a small endothermal peak.…”
Section: Dsc Analysis Resultsmentioning
confidence: 99%
“…The characterization of 'onium' salts as acids, per se, in the dry and fused state is one of the most useful extensions of the modern Br0nsted theory of acidity. Indeed, the very simplicity of this concept has caused it to escape investigation until now" (8).…”
mentioning
confidence: 99%